Aging Well Solutions to the Most Pressing Global Challenges of Aging - Galiana, Jean (Springer Nature, 2019)
This open access book outlines the challenges of supporting the health and wellbeing of older adults around the world and offers examples of solutions designed by stakeholders, healthcare providers, and public, private and nonprofit organizations in the United States. The solutions presented address challenges including: providing person-centered long-term care, making palliative care accessible in all healthcare settings and the home, enabling aging-in-place, financing long-term care, improving care coordination and access to care, delivering hospital-level and emergency care in the home and retirement community settings, merging health and social care, supporting people living with dementia and their caregivers, creating communities and employment opportunities that are accessible and welcoming to those of all ages and abilities, and combating the stigma of aging. The innovative programs of support and care in Aging Well serve as models of excellence that, when put into action, move health spending toward a sustainable path and greatly contribute to the well-being of older adults.